1989
DOI: 10.1002/1097-0142(19890601)63:11<2247::aid-cncr2820631132>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic assessment of cancer risk in oral precancerous lesions in India with special reference to nodular leukoplakia

Abstract: A cohort of 12,212 tobacco users was followed up annually to assess malignant potential of oral precancerous lesions in the Ernakulam district in Kerala, India. A total of 19 new oral cancers were diagnosed over a period of 8 years, and 15 (79%) of these arose from some preexisting precancerous lesion or condition. Nodular leukoplakia showed highest rate of malignant transformation (16% per year) as six of 13 nodular leukoplakia underwent malignant transformation over a mean follow-up period of 2.8 years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(78 citation statements)
references
References 13 publications
2
74
0
2
Order By: Relevance
“…It is characterized by the presence of wavy white lines that radiate from a central erythematous area and occurs at the site of betel quid placement (Avon, 2004). All the lesions were diagnosed in accordance with international recommendations (World Health Organization, 1977;Axell et al, 1984;Gupta et al, 1989;Mehta et al, 1993;Zain et al, 1996;Rajalalitha et al, 2005).…”
Section: Screening Programmementioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by the presence of wavy white lines that radiate from a central erythematous area and occurs at the site of betel quid placement (Avon, 2004). All the lesions were diagnosed in accordance with international recommendations (World Health Organization, 1977;Axell et al, 1984;Gupta et al, 1989;Mehta et al, 1993;Zain et al, 1996;Rajalalitha et al, 2005).…”
Section: Screening Programmementioning
confidence: 99%
“…The concept of certain precancerous lesions proceeding into oral cancer has long been accepted (Gupta et al, 1989;Yen et al, 2007). According to a workshop co-ordinated by WHO in May 2005 at London the use of the term 'Potentially malignant disorders' was recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the natural history of oral SCC is not fully understood (Napier and Speight, 2008;Scully & Bagan 2009), but current knowledge suggests that oral SCC develops in a stepwise process characterised by the initial presence of precursor cells and possibly lesions that subsequently (Reibel, 2003;Braakhuis et al, 2004;Angadi et al, 2012). Several studies have shown that many oral SCCs are preceded by identifiable precursor lesions or conditions (Gupta et al, 1998;Schepman et al, 1999;Warnakulasuriya et al, 2007). The term "oral potentially malignant disorders" (OPMD) was adopted by the World Health Organisation (WHO) in 2005 to describe oral lesions and conditions associated with a risk of malignant transformation (van der Waal, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These villages were in the broad study area of a large-scale epidemiologic study of oral cancer, as described elsewhere (Gupta et al, 1989). Speci®c factors that are of interest include: day-of-the-week effects; sequence (ie the placement in the series of 24 h diet recall interviews from which the nutritional data were derived); season; region (for the combined analysis only); subject (ie inter-person) variability; and residual (ie intra-person) variability.…”
Section: Introductionmentioning
confidence: 99%